Advanced Multimedia and Ubiquitous Engineering MUE/FutureTech 2018 - Park, James J.; Loia, Vincenzo; Choo, Kim-Kwang Raymond; Yi, Gangman; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents the combined proceedings of the 12th International Conference on Multimedia and Ubiquitous Engineering (MUE 2018) and the 13th International Conference on Future Information Technology (Future Tech 2018), both held in Salerno, Italy, April 23 - 25, 2018. The aim of these two meetings was to promote discussion and interaction among academics, researchers and professionals in the field of ubiquitous computing technologies. These proceedings reflect the state of the art in the development of computational methods, involving theory, algorithms, numerical simulation, error and uncertainty analysis and novel applications of new processing techniques in engineering, science, and other disciplines related to ubiquitous computing.
Keywords: Telecommunication; Computational intelligence; Computer networks .; Communications Engineering, Networks; Computational Intelligence; Computer Communication Networks